Kajian produktivitas pekerjaan pemasangan pelat struf pracetak pada bangunan gedung berdasarkan laporan - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Pertanian UGM, 1998)
ABSTRACT Utilization of precast concrete as structural slab is considered as one of solutions of construction industry productivity improvement problems which is slowly growing than those of manufacturing industry. To determine the level of productivity as well as its improvement rate, it is essential to have some kind of productivity measurement. The existence of project historical data such as those in daily progress report is deemed as an alternative basic measurement especially in lack of observed object conditions. This paper presents an attempt to analyze installation of precast structural slab productivity based on gathered informations from daily progress report. Keywords: precast concrete, productivity, progress daily report.